Evaluasi Ketahanan Hibrida Hasil Persilangan Kacang Hijau dan Kacang Uci terhadap Callosobruchus chinensis L. (Coleoptera: Bruchidae) - Lestari Ujianto; Nur Basuki; . Kuswanto; Astanto Kasno (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
The adzuki bean weevil Callosobruchus chinensis is the main pest of mungbean especially during seed storage. Mungbean generally has low yield and is susceptible to main pests. Ricebean (Vigna umbellata (Thunb.) Ohwi & Ohashi) has superior characters such as the high pod number per plant and resistance to many pests. The interspecific hybridization was conducted to combine the superior characters of mungbean and ricebean. The objectives of this research were to evaluate resistance of hybrids of interspecific hybridization between mungbean and ricebean to C. chinensis and to determine pattern of resistant inheritance. Evaluation of resistance to this pest was conducted in bottles by placing 200 hybrid seeds and then 20 C. chinensis adults were introduced into the bottle covered by dense cheese cloth. The bottles were arranged in a completely ramdomized design with three replications. The treatment consisted of eight hybrids and six parents. The results showed that the resistance of the test hybrids to C. chinensis was different among cross combinations. Hybrids of crossing between mungbean Merak variety and yellow ricebean as well as Vima variety and red ricebean were moderately resistant, while the others were resistant. There was resistance improvement of hybrids to C. chinensis. The resistance of the hybrids to C. chinensis was controlled by single gene with partially dominance gene action.